Strategi Komunikasi Politik dalam Kampanye Digital: Studi Kasus Pemilihan Gubernur DKI Jakarta - Jihan; Linda Susanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The development of digital technology has revolutionized political campaign strategies, particularly in regional elections. The Jakarta gubernatorial election serves as a case study to analyze how digital platforms have reshaped political communication. This study investigates the use of social media, digital advertising, and online engagement in influencing voter preferences. Political candidates increasingly rely on digital tools to reach a wider audience, personalize campaign messages, and counter political narratives. The interactive nature of social media also allows candidates to foster direct communication with voters, enhancing their political image and credibility. This research employs a qualitative approach, utilizing content analysis of campaign materials and interviews with political communication experts. The findings reveal that successful candidates effectively integrate digital platforms to build voter trust, mobilize supporters, and manage political discourse. Social media algorithms, targeted advertising, and viral content play crucial roles in shaping public perception. The study concludes that digital campaign strategies have become a decisive factor in election outcomes, emphasizing the need for politicians to adapt to the evolving digital landscape.